Basic Evaluation of Solar Energy Utilization in Gas Pressure Reduction Stations for Fuel Consumption Reduction - Dheyaa Abdulameer Ismael (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Natural gas pressure reduction stations (PRS) consume fuel for gas preheating, causing CO₂ emissions. Specific Background: The Joule-Thomson effect cools gas during throttling, requiring continuous heating to prevent hydrates. Knowledge Gap: Few studies assess solar-assisted PRS performance under real conditions. Aims: This study evaluates parabolic trough collectors (PTCs) with thermal storage for preheating in PRS. Results: The system saves 40% fuel (256,000 m³/year), reduces CO₂ by 14,000 tons, and achieves 11.5% IRR with a 4.5-year payback. Novelty: It integrates validated transient modeling for practical scalability. Implications: Solar thermal integration provides an effective strategy to decarbonize gas infrastructure and enhance energy efficiency. Solar thermal integration in pressure reduction stations achieves 40% fuel savings and significant CO₂ emission reduction. The system shows strong economic performance with an IRR of 11.5% and a 4.5-year payback period. The approach supports sustainable and scalable solutions for gas infrastructure decarbonization. Keywords : Solar thermal energy, Natural gas pressure reduction, Fuel consumption reduction, Exergy analysis, CO₂ emissions